Concrete paving blocks abrasion resistance: ecuadorian standard application and modification - Realpe Rivadeneira, Guillermo Ricardo (2020)
The quality control of concrete paving blocks in Ecuador has remained unchanged since 1987, using as a criterion of quality and durability the value of the compressive strength of the block under the concept of global indicator. This indicator assumes that when the axial load carrying capacity specification is met, it will cover requirements such as abrasion resistance, therefore the expectations of the paving surface design life. However, in recent years an early deterioration of the paving brick surfaces has been verified in general despite compliance with the axial load carrying capacity requirements established in the Ecuadorian standard. Under these conditions, the University, the construction industry and the Ecuadorian Standardization Institute (INEN) decided to adapt a new control standard in which the indicator of acceptance is broken down into several physical and mechanical parameters, using the European standard EN 1338 as a reference document. Among the parameters, the quantification and assessment of abrasion resistance became of greater interest, both because of the lack of abrasion resistance of most of the production in the country, as well as the test method to be used. The present article, based on a traditional statistical analysis of 516 abrasion resistance tests by means of the wide wheel abrasion test method (EN 1338) performed at the Construction Materials laboratory of the Pontifical Catholic University of Ecuador (PUCE) between 2010 and 2015, verified the symmetrical normal distribution behavior of the two lots in which the data were classified; one corresponding to plants that maintain quality control processes and another to plants without control in addition, quantified the characteristic tyre track value according to the abrasion test in the analysis period. Through the information obtained, the need for abrasion control has been justified, as well as the recommendation to establish a specification for Ecuador, different from that established in the European standard